Infección por Angiostrongylus cantonensis (Nematoda: Metastrongylidae) en Rattus rattus (Rodentia: Muridae) en una localidad de La Habana, Cuba - Companioni, Ariamys; Peraza, Jennys; Meléndez, Zulema; Gonzalez, Aileen; Lopez, Ledy Xiomara; Rodriguez, Ana Elisa; Cantillo, Jorge Demetrio; Nuñez, Fidel Angel (2019)
Introduction: Eosinophilic meningitis caused by Angiostrongylus cantonensis (Chen, 1935) is an emergent zoonosis present in Cuba. In the country, few studies about the prevalence of infection in definitive hosts, which can determine risk sites for the establishment of effective measures to prevent the disease, have not been carried out so far. Objective: To determine the prevalence of infection with Angiostrongylus cantonensis in a natural population of Rattus rattus, its relationship with the population structure, and the season of the year in an urban farm field belonging to the Programme of Urban and Suburban Agriculture of Cuba. Material and Methods: A descriptive study was conducted in La Lisa Municipality, Havana, Cuba. The rats were collected monthly during the rainy and dry seasons. The pulmonary arteries of the captured rodents were examined for adult worms. The prevalence of parasitological indices was calculated. The frequencies of infection were compared between the seasons of the year and ecological ages. Results: A total of 63 rodents identified as Rattus rattus were captured. Of the total of individuals captured, 46.03% were infected with A. cantonensis, with an increase of infection in adult individuals (59.46%) and during the rainy season (55.88%). Conclusions: The infection of A. cantonensis in its definitive host R. rattus, and its circulation in the study area in the analyzed period was demonstrated for the first time in Cuba. The presence of adult rats, the high quantity of rodents and the rainy season were the factors that contributed to a greater infection of A. cantonensis, which increase the probability of transmission to intermediate hosts, and consequently, the risk of transmission to humans. Keywords: Angiostrongylus cantonensis, rodents, Rattus, urban field, rainy period. Introducción: La meningoencefalitis eosinofílica producida por Angiostrongylus cantonensis (Chen, 1935), es una zoonosis emergente presente en Cuba. En el país existen escasos estudios de prevalencia de infección ...